Alcohol-related crime or no crime because of the perpetrator’s (factual) insanity? - Anna Danuta Golonka (Oñati Socio-Legal Series)
The criminal liability of the perpetrator of a criminal act is not only conditioned on the objective features of the criminal act but also on the subjective ones (intentional or unintentional behavior). Apart from the subjective features of the act, guilt is also necessary in order to be able to attribute the crime. However, both theory and practice face with one exception to the principle of nullum crimen sine culpa (no crime without guilt). This applies to a state of disturbances of mental functions caused by the perpetrator of a criminal act. There are numerous problems arising from the collision of the need to punish the perpetrator (dictated by criminal policy), and the real state of his/her psyche, which can sometimes speak even for no fault (and thus no crime). It has a significant meaning for the subjective aspects of the crime. The aim of this study is to present these problems based on a dogmatic and legal analysis of regulations and a review of the literature in the field of medicine. The final conclusions lead to a de lege ferenda postulate concerning the legal solution of the above-mentioned dilemmas.